Archean-Paleoproterozoic crustal evolution of the Ordos Block in the North China Craton: Constraints from zircon U-Pb geochronology and Hf isotopes for gneissic granitoids of the basement - Zhang, C.; Diwu, C.; Kröner, A.; Sun, Y.; Luo, J.; Li, Q.; Gou, Long-Long; Lin, H.; Wei, X.; Zhao, J. (Elsevier BV, 2015)
The Ordos Block has been considered as an Archean micro-block in North China Craton. However, its formation and evolution are poorly understood for a long time due to lack of available basement rocks. Our LA-ICPMS and SIMS zircon U-Pb dating of gneissic granitoids from the Ordos Block basement identified two distinct periods of granitic magmatism at ~2.5Ma and 2.2-2.0Ga, and two phases of metamorphisms at ~1.95Ga and ~1.85Ga, respectively. Of which most zircons of ~2.5Ga granitoids show positive eHf(t) values ranging from +0.1 to +4.1 with a peak TDM of ~2.7Ga. Minor zircons have negative eHf(t) values from -3.8 to -0.02 and THfC of 2.8-3.1Ga. Moreover, the 3.40Ga inherited zircon and zircons with THfC of 3.1-4.2Ga were found from 2.2Ga to 2.0Ga granitoids. These suggest that there existed a Neoarchean crust in the Ordos Block, which underwent a major crustal growth at ~2.7Ga and granitic magmatism at ~2.5Ga, highly consisting with ~2.7Ga crustal growth and ~2.5Ga magmatism resulted from juvenile crustal reworking in North China Craton. The zircons from 2.2Ga to 2.0Ga granitoids in Ordos Block basement display variable Hf isotopic composition of positive to negative eHf(t) values, much similar to those of 2.2-2.0Ga granitoids related to continental margin arc setting in the Trans-North China Orogen. They were subsequently subjected to ~1.95 and ~1.85Ga metamorphisms, which were widespread throughout the Trans-North China Orogen. Based on the highly coherent zircon geochronology and Hf isotopic composition between Ordos Block and other micro-blocks of North China Craton, we propose that there is a Neoarchean crust in Ordos Block, which underwent a tectonic evolution similar to those in East Block in later Neoarchean, and then experienced 2.2-2.0Ga granitic magmatism related to continental margin arc and 1.95-1.85Ga metamorphism resulted from collision between the East and West Blocks along TNCO.